A Doubly Salient Starter/Generator With Two-Section Twisted-Rotor Structure for Potential Future Aerospace Application - Chen, Zhihui; Wang, Huizhen; Yan, Yangguang (IEEE transactions on industrial electronics (1982), 2012)
The starter/generator is one key technology for the more electric/all electric aircraft. The wound-field doubly salient starter/generator supplies good prospect in the aircraft application. The doubly salient starter/generator prototype is modeled for simulation. The electromotive force (EMF) waveforms obtained from simulation are validated by the experiments. Based on the EMF waveforms of the machine, the standard three-step control algorithm is derived. When the rotor runs at high speed, the advanced angle control (AAC) method is adopted to get enough torque. The simulation and experiment results with two different control strategies are compared. The AAC scheme can increase the average torque by 62.7% at 3600 r/min. To reduce the torque ripples, the two-section twisted-rotor structure is adopted. The analysis shows that the two-section twisted-rotor structure helps to reduce the torque ripple coefficient by more than 50%. The two-section twisted-rotor structure is also helpful to reduce the output dc voltage ripple.